PENGARUH SISTEM ONLINE TICKETING TERHADAP KEPUASAN PELANGGAN DI TRAVEL SKY CONEXXION MANADO - Bet El Lagarense; Merry Adrah; Troy J. Rondonuwu (Jurnal Ilmu Pariwisata, 2023)
In globalization era, the needs of a person or a group are getting bigger and to fulfill these needs, producers must always improve their services. One of the human needs is recreation or travel, and therefore humans will look for a reference and means to fulfill their needs in traveling. One of the subjects that can meet the needs of infrastructure for travel is the Travel Agent. Travel agents who used to use a manual system have evolved into an online system to make reservations easier and registration faster. The aim of this research is to find out how much influence the Online Ticketing System has on customer satisfaction at Travel Sky Conexxion Manado. Based on the calculation method using Simple Linear Regression Analysis, the results obtained is : Y = 13.90 + 0.66X, and the Correlation Coefficient Number is r = 70.47 which shows that between the online ticketing system (variable X) and customer satisfaction (variable Y) there is a positive correlation, meaning that if the online ticketing system runs smoothly, customer satisfaction will increase by 70.47. Based on the research results, it can be concluded that the existence of an online ticketing system makes reservations easier and registration faster which makes customers more satisfied.